Desinformação e vulnerabilidades com relação à sexualidade dos adolescentes e jovens da Reserva de Mamirauá, Amazonas – Brasil : Misinformation and vulnerabilities of the adolescents and young people living at the Reserva Mamirauá, Amazonas - Brazil - Ruzany, Maria Helena; Tavares Andrade, Carla Lourenço de; Meirelles, Zilah Vieira; F. Moura, Edila Arnaud; Deusdará, Rodolfo; Rodrigues, Vandrea; Bezerra da Silva, Maria Mercês; de Lima, Daniela Pereira (Adolescência e Saúde, 2010)
Objective: To present a study about reproductive health and sexuality of adolescents and young people living at the riverside in the Reserva de Desenvolvimento Sustentável Mamirauá, Amazonas/Brazil. Methods: It was conducted an epidemiologic inquiry, using a questionnaire about sexuality and reproductive health. We interviewed 118 people, ages between 10 and 24 years old, in fi ve communities in the rural areas. It was studied the categorical data using the chi square test, with 5% of signifi cance level. Results: The riverside family is numerous, nuclear type and the masculine fi gure is the chief of the family and responsible for the children. Regarding sexuality, 52.7% of the girls and 47.3% of the boys had begun sexual activity (p<0,001). Among them, 86.2% of the girls and 92.3% of the boys were using condoms, although only 25.4% were always using it. Inquiring the entire group, 97.3% didn’t know about double protection; 90% never heard about emergency contraception and 85.5% didn’t know anything about how is the transmission of Aids disease. Conclusion: The youth living in the rural area of the Amazonia forest need professionals prepared to develop activities of health promotion and prepared to debate about sexuality and DST/Aids prevention. Besides, is ur gent the development of public policies to improve the quality of life and to give support to the vulnerable groups of those regions.